Assessment of the genetic relationship of Turkish olives (Olea europaea subsp europaea) cultivars based on cpDNA trnL-F regions - (:unkn) unknown (UNIV ZAGREB, FAC SCIENCE, DIV BIOLOGY, 2018)
The olive tree (Olea europaea L.) is one of the major cultivated species in the world, and Mediterranean countries produce about 90% of world cultivated olives. In this study, the genetic relationship of seven Turkish olive cultivars was investigated using non-coding trnL-F regions in chloroplastic genome. Cultivars demonstrated a similar sequence length of 330-340 bp with an average 35.26% G+C content. Variable (polymorphic/segregating), parsimony informative and total numbers of the insertion or the deletion of bases in the DNA (indel sites) were 4, 3, and 28, respectively. Nucleotide diversities p and. were found as 0.00631 and 0.00644 respectively, while Tajima's D was -0.786. cpDNA trnL-F regions of sequenced Turkish olive cultivars had a low level of genetic variations, and these non-coding regions were strictly conserved in all analyzed cultivars. Geographically distant shared more sequence similarities than relatively close cultivars. The phylogenetic analyses indicated that the biogeographic distribution of cultivars does not demonstrate any association inferring cultivar source. These results indicate the possibility of germplasm exchanges among countries or that some indel mutations contribute to variations of the Turkish olive gene pool. Thus, the authorities should develop the necessary programs to preserve the purity of native germplasms.
Keywords: germplasm; intergenic; lineage; non-coding trnL-F; pairwise; plastome; CHLOROPLAST-DNA; L.; SEQUENCES; DIVERSITY; REPEATS; RAPD